Odnos do zdravil in sodelovanje bolnikov s hipertenzijo pri zdravljenju z zdravili v Sloveniji - Kodrič, Ana (Farmacevtski vestnik, 2020)
We conducted a study in community pharmacies in Slovenia with the aim of evaluating the hypertensive patients' medication beliefs and their impact on medication adherence and blood pressure control. Medication beliefs were evaluated by Beliefs about Medicines Questionnaire, and medication adherence was evaluated by pill count. A total of 117 patients were enrolled in the study. 30.2% of patients do not recognise the need to take blood pressure lowering medicines and in 12.9% of patients, concerns about taking them outweigh the perception of benefits. 3.4% of patients are sceptical, 11.2% ambivalent, 26.7% indifferent and 58.6% are accepting regarding their blood pressure lowering therapy. Medication beliefs have an impact on medication adherence, since patients who are concerned about taking antihypertensive medications are less likely to take them regularly. Medication adherence is 16.5% higher in accepting patients nd 18.7% higher in indifferent patients than in ambivalent patients. Results also indicate the impact of medication beliefs on blood pressure control in patients with hypertension.
Keywords: hipertenzija; Hipertenzivna srčna bolezen; Krvni tlak; odnos do zdravil; sodelovanje pri zdravljenju